2017
DOI: 10.1177/0020764017733765
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic-like experiences in help-seeking adolescents: Dimensional exploration and association with different forms of bullying victimization – A developmental social psychiatry perspective

Abstract: In total, 50 PLE-positive adolescents screened from 324 HS adolescents (15.4%) constituted the sample. Paranoia and verbal bullying were the PLEs and form of victimization most represented, respectively. Verbal bullying was strongly associated with paranoia (odds ratio (OR): 4.40, confidence interval (CI): 2.8-5.9, p < .001). Results remained significant after controlling for confounder (socio-demographic, anxiety, depression and for the latter analysis also other forms of victimization). Furthermore, social m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
3
13
1
Order By: Relevance
“…Results demonstrated that paranoia was dimensionally distributed in adolescent with AN and/or ED NOS. Our descriptive were higher than those of Ronald et al (mean 12,14 and median 10,00) in the general population but lower than in adolescent help seeking screened positive for PLEs (mean 34.64 and median 38) (22,23). This may have importance because EDs population could potential be at risk for psychotic symptoms (5).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Results demonstrated that paranoia was dimensionally distributed in adolescent with AN and/or ED NOS. Our descriptive were higher than those of Ronald et al (mean 12,14 and median 10,00) in the general population but lower than in adolescent help seeking screened positive for PLEs (mean 34.64 and median 38) (22,23). This may have importance because EDs population could potential be at risk for psychotic symptoms (5).…”
Section: Discussioncontrasting
confidence: 65%
“…. We already used this scale for other study (23). Other variables we collected demographical and personal data from patient's clinical records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reported the term as belonging outside of psychotic disorders . Definitions included ‘psychotic symptoms experienced by a part of the healthy population without frank disorder’, ‘subclinical psychotic phenomena like perceptual anomalies and delusion‐like experiences in the absence of manifest psychotic illness’, and ‘mild and/or transient forms of the experiences and symptoms reported by schizophrenia patients’ found among ‘psychosis‐prone individuals’ . Psychotic experiences and PLE have similarly been considered as psychotic symptoms ‘in an attenuated form’, and ‘experiences hallucinatory or delusional in nature but with reality testing remaining intact.’ PLE are also defined as ‘mild versions of psychotic symptoms’ .…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence on the thematic continuity (thematic link) between the stressful experiences of life and the contents of delusional thinking [ 12 ]; furthermore, stressful experiences could not only play a role in the development of psychotic symptoms, but also may shape their contents and form [ 12 , 13 ]. From this perspective, in a developmental social psychiatry framework, verbal and social bullying and paranoia are strictly associated, as seen in a sample of help-seeking adolescents who have had PLEs [ 14 ]. To continue on this path, we used a model that includes not only the presence of paranoid thoughts but also the content of those thoughts.…”
Section: Introductionmentioning
confidence: 99%